Successful Management of a Combined Abdominal and Thoracic Trauma with Rectal Impalement: Report of a Case. (17th June 2013) - Kasapas, Konstantinos; Daskalaki, Anna; Kaimasidis, George; Chalkiadakis, George
Abstract : Introduction . Combined abdominal and thoracic impalement injuries are a rare form of penetrating trauma. Nowadays, they occur more frequently as an accident and not so often as a deliberate violent action. Case Report . A 35-year-old man was admitted to our emergency department with chest pain and respiratory distress after he had reportedly slipped in his bathtub. Abdominal and thoracic imaging, including computed tomography (CT), confirmed a right-sided pneumothorax and a liver laceration without bleeding or further endoperitoneal trauma. A chest tube was placed. During his hospitalization in the first 24-hour period, he complained of abdominal and right shoulder pain accompanied by fever. A new abdominal and thoracic CT scanning revealed a rupture of the rectosigmoid, a rupture of right hemidiaphragm, and a foreign body in the thoracic cavity. The patient admitted that a broomstick was violently placed through his rectum, and he underwent a thoracotomy with an exploratory laparotomy. The foreign object was removed, the diaphragmatic rupture was repaired, and a Hartmann's procedure was performed. The postoperative course was uneventful. Conclusion . In cases of combined thoracoabdominal trauma, high index of suspicion is required when medical history is misleading and the injuries are not obvious immediately. A coordinated team effort in a well-organized trauma center is also very important.